Effect of Sugars on the Thermal Stability of Hen Lysozyme both in the Absence and Presence of Denaturants - Joshi, Reena (My University, 2013)
The present work showed the effect of sugars on the thermal stability of native lysozyme (pH 4.5) both in the absence and presence of sugars. The thermal stability of the protein was found to increase in the presence of sugar. Among the sugars used (trehalose, sucrose, glucose and maltose), the thermal stability of the protein is increased more for trehalose and least for glucose. The stabilizing effect of sugars is mainly due to preferential hydration of protein or the preferential exclusion of the sugars [45]. In contrast to sugars, GdnHCl has been found to decrease the thermal stability of the protein. The destabilizing action of GdnHCl is attributted mainly to their ability to bind to the protein [41-43]. The effect of sugars on the thermal stability of lysozyme in the presence of GdnHCl is also examined. The inclusion of sugars results in the counteraction of the destabilizing effect of the GdnHCl. This may be attributed to the fact that the addition of sugars alters the balance between the preferential binding of GdnHCl and preferential exclusion of sugars, resulting in the increased hydration of the protein and thus helps in the counteraction of the destabilizing action of the GdnHCl. It is also observed that the counteraction effect of sugars on the destabilizing effect of the GdnHCl is more pronounced for trehalose and least for glucose.
MS, SCBC
Keywords: Thermal Stability Hen Lysozyme; Denaturants Sugars